Overcoming Challenges in Pediatric Formulation with a Patient-Centric Design Approach: A Proof-of-Concept Study on the Design of an Oral Solution of a Bitter Drug - John Dike N. Ogbonna; Edite Cunha; Anthony A. Attama; Kenneth C. Ofokansi; Helena Ferreira; Susana Pinto; Joana Gomes; Ítala M. G. Marx; António M. Peres; José Manuel Sousa Lobo; Isabel F. Almeida (MDPI AG, 2022)
Designing oral formulations for children is very challenging, especially considering their peculiarities and preferences. The choice of excipients, dosing volume and palatability are key issues of pediatric oral liquid medicines. The purpose of the present study is to develop an oral pediatric solution of a model bitter drug (ranitidine) following a patient centric design process which includes the definition of a target product profile (TPP). To conclude on the matching of the developed solution to TPP, its chemical and microbiological stability was analyzed over 30 days (stored at 4 °C and room temperature). Simulation of use was accomplished by removing a sample with a syringe every day. Taste masking was assessed by an electronic tongue. The developed formulation relied on a simple taste masking strategy consisting in a mixture of sweeteners (sodium saccharine and aspartame) and 0.1% sodium chloride, which allowed a higher bitterness masking effectiveness in comparison with simple syrup. The ranitidine solution was stable for 30 days stored at 4 °C. However, differences were noted between the stability protocols (unopened recipient and in-use stability) showing the contribution of the simulation of use to the formation of degradation products. Stock solution was subjected to acid and alkali hydrolysis, chemical oxidation, heat degradation and a photo degradation stability assessment. The developed pediatric solution matched the TPP in all dimensions, namely composition suitable for children, preparation and handling adapted to hospital pharmaceutical compounding and adequate stability and quality. According to the results, in-use stability protocols should be preferred in the stability evaluation of pediatric formulations.